2002
DOI: 10.1097/00006454-200209000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Population-based epidemiologic study of tinea pedis in Israeli children

Abstract: The prevalence of tinea pedis in children has increased in recent decades in Israel and should be considered in the differential diagnosis of dermatologic diseases affecting the feet. Washing habits have a significant effect on tinea pedis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…15 In our study, 7 cases presented lesions on the sole of the foot, and all cases had lesions in the area between the toes.…”
Section: Discussionmentioning
confidence: 46%
“…15 In our study, 7 cases presented lesions on the sole of the foot, and all cases had lesions in the area between the toes.…”
Section: Discussionmentioning
confidence: 46%
“…9 In another study of 1148 Israeli children, tinea pedis (found in 6.9%) was increased with patient-reported HH. 10 In contrast, an Italian survey of 1024 young adults found that tinea pedis (28 cases) had no correlation with patient-reported HH. 11 Similarly, a single observational study of 53 patients with pitted keratolysis found that plantar HH was commonly present but did not evaluate the degree of risk.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have shown a significant correlation between the two conditions [15, 39], other authors have not confirmed any such connection [18, 27, 31, 40]. …”
Section: Discussionmentioning
confidence: 99%